PRODUCTION AND IMPLEMENTATION OF SCIENCE COMICS TO ENHANCE SCIENCE LEARNING FOR ELEMENTARY SCHOOL STUDENTS AT SDN 27 PEUSANGAN - Kiki Fajariani; Khairunnisak (Jurnal Pengabdian Bangsa, 2026)
This community service program aimed to produce and implement science comics to enhance science learning for elementary school students at SDN 27 Peusangan. Science learning at the elementary level often faces challenges related to low student engagement and limited use of attractive learning media. To address these issues, science comics were developed as an innovative learning medium that integrates scientific concepts with visual storytelling tailored to students’ characteristics. The implementation stages included needs analysis, comic design and production, teacher assistance, classroom application, and evaluation. The results showed that the use of science comics increased students’ learning motivation, active participation, and understanding of basic science concepts. In addition, teachers demonstrated improved competence in utilizing creative learning media to support classroom instruction. Overall, science comics proved to be an effective and engaging learning medium for elementary science education and have the potential to be sustainably implemented in primary schools.